Trypa-NO! contributes to the elimination of gambiense human African trypanosomiasis by combining tsetse control with “screen, diagnose and treat” using innovative tools and strategies - Ndung’u, Joseph Mathu; Boulangé, Alain; Picado, Albert; Mugenyi, Albert; Mortensen, Allan; Hope, Andrew; Mollo, Brahim Guihini; Bucheton, Bruno; Wamboga, Charles; Waiswa, Charles; Kaba, Dramane; Matovu, Enock; et al. (PLOS Neglected Tropical Diseases, 2020)
null